Innovation and Burden Sharing Strategy to Internationalize Batik: Case Study of Laweyan Batik - Susiatiningsih, Rr. Hermini; Alfian, Muhammad Faizal; Setiyaningsih, Dewi (Dinamika Kerajinan dan Batik: Majalah Ilmiah, 2024)
Batik has added economic value as a cultural heritage, making it marketable at domestic and international levels. The most significant benefits of promoting batik products to the global market are bringing local values to global society, as well as the benefits of economic development for the domestic garment industry. Laweyan is one of the Solo districts specializing in batik cloth production. The sector in Laweyan produces painted and printed batik cloth, distributed not only in the local market but also in the global market. By using qualitative methods, this research analyses the innovation of batik products and marketing innovations of Batik Laweyan in penetrating the global market. The findings from this research conclude that producers in Laweyan Regency develop product innovations by adapting batik motifs with local nuances to international market tastes, and to encourage internationalization, producers use marketing innovations through a burden-sharing strategy. So, in terms of internationalization, local cultural values become an essential aspect of product innovation. In contrast, in terms of marketing, the burden-sharing strategy becomes an innovation to penetrate international markets. Through the burden-sharing approach, local producers build networks with foreign producers to obtain demand from foreign markets so that local producers can reach the world market by bridging the local industry and international markets.